STUDI FAKTOR CONTAINER INDEX, HOUSE INDEX, PERILAKU HIDUP BERSIH DAN SEHAT, PRAKTIK BUANG SAMPAH, TINGKAT STRESS DAN KEJADIAN DBD DI KOTA SEMARANG - Jeany Rahma Nafizar; Nur Endah Wahyuningsih; Mateus Sakundarno Adi (Jurnal Kesehatan Masyarakat (Undip), 2016)
Dengue Hemorrhagic Fever (DHF) is a disease caused by dengue virus is classified Arthropod-Borne Virus, genus Flavivirus and family Flaviviridae. Dengue is transmitted by mosquitoes of the genus Aedes, principally Aedes aegypti or Aedes albopictus. DHF can occur throughout the year and can affect all age groups. DHF is a public health problem over the last 45 years ie since 1968 until today. Incidence Rate DBD Semarang in 2015 was ranked third IR DBD Central Java after Magelang, Jepara regency This study aims to describe the container index (CI), house index (HI), the behavior of clean and healthy living, practices trash, the level of stress and incidence of dengue in the productive age (15-59 years) in the city of Semarang. Research using this type of observational and descriptive cross-sectional design, with a purposive sampling techniques. The sample in this study are patients with DHF at the Regional General Hospital (Hospital) Tugurejo Semarang, Central General Hospital (Dr) dr. Kariadi, Regional General Hospital (Hospital) Semarang, and Hospital Telogorejo in March-May 2016 that met the inclusion criteria as well as the non-sufferers of dengue in the city of Semarang in March-May 2016 that met the inclusion criteria. The results showed they found mosquito larvae in respondents with a high density level categories. In the group of patients with DHF, PHBS and Practices of  Empty Trash respondent good category higher than the category is not well. While the level of stress in the group of patients with DHF with lower stress category is higher than the low stress category.